The influence of migration on the burden of and response to infectious disease threats in China: A theoretically informed review - Chun Hao; Xia Zou; Guiye Lv; Megan McLaughlin; Xiaoming Li; Li Ling (United Nations Research Institute for Social Development (UNRISD), 2013)
Massive rural-to-urban migration in China may influence infectious disease spread, but the same powerful social forces that reliably promote migration can also be used to design more effective health systems. The authors systematically reviewed eight databases to identify research studies focused on migrant infectious disease epidemiology and control policies. They examined the sequential phases of rural-to-urban migration (pre-departure, travel, destination, interception, and return) in terms of their influence on infectious disease epidemiology and control policies. The migration process has a profound impact on the distribution of airborne, blood-borne, sexually transmitted, and mosquito-borne infectious diseases in addition to influencing potential control strategies. The spread of vaccine preventable diseases in China underscores the need for more responsive vaccination systems among migrants. Scaling up successful pilot migrant infectious disease control policies and new programmes are urgently needed in order to achieve health equity for Chinese migrants.
Keywords: 330